C-Breeze Smart Collar / Muhammad Luqman Ismadi, Damia Kamilia Ahmad … [et al.] - Ismadi, Muhammad Luqman; Ahmad, Damia Kamilia; Shaarani, Luqman Hariz (2017)
Due to the tropical and humid climate of Malaysia, Malaysians cannot get away from getting sweaty. Although human's body is preconditioned to sweat, it is noticeable that some individuals sweat more than the usual in comparison to others. The aim is to underline the issue of excessive sweating and design a product that could overcome the problem. The study's research method uses online survey through questionnaires for a better understanding on the issue of excessive sweating. The questionnaire survey is distributed to30 students of Faculty of Architecture, Survey and Planning (FSPU) in Universiti Teknologi MARA, Puncak Alam. Data is collected and discussed which further leads the team to the idea generation.A session of brainstorming is discussed in idea screening where the team has come up with options of possible products under different categories. Three products under the category of accessory is shortlisted and further voted in the market survey. The survey method that the team uses for this chapter is a face to face verbal interview. The team has interviewed ten of our studio mates in the Faculty of Architecture, Survey and Planning (FSPU) in Universiti Teknologi MARA, Puncak Alam. Smart Collar received the highest vote of 70 percent.In concept testing, a series of sketching processes is carried out to get the form and functions of the product. With the aid or rendering, 2D and 3D prototypes, the design of the product is finalized. A total of 10 sets of our product named 'C-Breeze Smart Collar' is distributed to ten of our studio mates that were interviewed earlier during market survey for a test marketing.